A Review of Evidence Concerning Changes of Climate in India during the Proto-historical and Historical Periods - Seth, S. K. (Indian Forester, 1962)
Archaeological, historical, literary, sculptural and scientific evidence has been sifted in order to determine if any provable change of climate has taken place in the Indo - Pakistan subcontinent during the proto-historical and historical periods, whether the flora has changed significantly, and finally whether there has been a natural change in climatic conditions leading to vegetational adjustments or, contrariwise, the interference with natural vegetation has caused a deterioration in the prevailing climate. The archaeological evidence mainly relates to the Indus civilization period whereas literary and historical sources have been employed for the later historical period. Available data regarding plant and animal remains have been considered. The characteristics of the desert and the changes in its drainage pattern have been discussed and the theories postulating a recession of the monsoon belt have been briefly considered. It is concluded that while there is likelihood of climate having changed somewhat, especially in the Lower Indus Valley and Rajasthan, the destruction of vegetation has materially contributed to the deterioration in the climatic conditions. In the rest of the country, the extermination of native vegetation over large tracts has been the main factor responsible for worsening the environmental conditions and causing a consequent change in the succeeding flora.